Revisiting the multidecadal variability of North Atlantic Ocean circulation and climate - Mishonov, Alexey; Seidov, Dan; Reagan, James (Frontiers in Marine Science, 2024)
The World Ocean’s surface, particularly in the North Atlantic, has been heating up for decades. There was concern that the thermohaline circulation and essential climate variables, such as the temperature and salinity of seawater, could undergo substantial changes in response to this surface warming. The Atlantic Meridional Overturning Circulation (AMOC) has changed noticeably over the last centennial and possibly slowed down in recent decades. Therefore, concerns about the future of the North Atlantic Ocean climate are warranted. The key to understanding the North Atlantic current climate trajectory is to identify how the decadal climate responds to ongoing surface warming. This issue is addressed using in-situ data from the World Ocean Atlas covering 1955-1964 to 2005-2017 and from the SODA reanalysis project for the most recent decades of 1980-2019 as fingerprints of the North Atlantic three-dimensional circulation and AMOC’s dynamics. It is shown that although the entire North Atlantic is systematically warming, the climate trajectories in different sub-regions of the North Atlantic reveal radically different characteristics of regional decadal variability. There is also a slowdown of the thermohaline geostrophic circulation everywhere in the North Atlantic during the most recent decade. The warming trends in the subpolar North Atlantic lag behind the subtropical gyre and Nordic Seas warming by at least a decade. The climate and circulation in the North Atlantic remained robust from 1955-1994, with the last two decades (1995-2017) marked by a noticeable reduction in AMOC strength, which may be closely linked to changes in the geometry and strength of the Gulf Stream system.